Plan de ordenamiento turístico para el desarrollo de la parroquia Ricaurte del cantón Chone - Véliz Velásquez, Priscilla Alejandra (2023)
This work was carried out with the purpose of designing a territorial tourism management plan for the development of the Ricaurte parish in Chone canton, being a documentary-bibliographical and field research, with an exploratory-descriptive approach based on analytical-synthetic and descriptive methods, which allowed to know the reality of the area under study and the incidence that it has. Four phases were projected; in the first one, a characterization of the territory and a multidimensional analysis were carried out using matrixes and mapping of actors; at the same time, 156 surveys were applied to the population of the parish which was in charge of knowing the perception regarding tourism. In the second phase, the evaluation of tourist resources was carried out through bibliographic review, observation and application of the potential matrix. In the third phase, we proceeded with the systematization of the problems and potentialities of the parish through a SWOT analysis, (EFI, EFE, internal and external matrixes). Finally, in the fourth phase, the tourism management plan was developed using matrixes and maps for the distribution of tourism resources and environmental units. It was possible to determine that Ricaurte has limitations in its local development due to the lack of support in the planning of strategies by the GAD. At the same time, there is a lack of services for the generation of tourist activities and there is difficulty in accessibility to resources and attractions. The territorial ordering plan presents viable strategies, programs and projects that contribute to the living conditions of the inhabitants and the strengthening of tourism development.